Tourism Resilience in CALABARZON Region Philippines - Rosan Olalia (Universidade Estadual de Alagoas, 2024)
This research explores the tourism resilience of Resort Hotels in Region IV - A or CALABARZON which comprises 6 provinces namely, Cavite, Laguna, Batangas, Rizal and Quezon. This region is one of the tourism hot spots in Philippines and it is also susceptible to disasters like volcanic eruption, earthquake, flooding of its coastal areas and one of the most affected areas in Philippines next to National Capital Region by COVID-19 pandemic. According to the CALABARZON Regional Development Plan 2023-2028 prepared by the National Economic Development Authority (NEDA), the escalating losses and damages incurred because of disasters underscore the imperative of fostering resilience within this region. It is important to measure the resilience of tourism enterprises as it is vital in determining their capability and capacity to cope up and recover from the socio-economic impacts caused by these disasters. A total of 101 Department of Tourism (DOT) accredited accommodation establishments have participated in the study which were represented by their respective managers. The researcher measured the tourism resilience index of resort hotel industry of Region IV A (CALABARZON) using six (6) indicators namely, business operational resilience, disaster preparedness, marketing, workforce, use of national and local resources, and resource access and knowledge adopted from Tourism Resilience Index developed by Mississippi Alabama Sea Grand (MASGP) and National Oceanic and Atmospheric Administration of US Department of Commerce (NOAA). Moreover, comparison on the tourism resilience assessment of resort hotels when grouped according to their enterprise profile and managers profile was further analyzed.